Prevailing patterns of the sound speed distributions in the environment of the Southern Baltic - GRELOWSKA, G. (Archives of Acoustics, 2000)
The paper contains the results of experimental and theoretical research aimed at elaborating characteristic features of the acoustic conditions in the Southern Baltic. As there features are fully dependent on the hydrological conditions, the sound speed distribution is influenced by many factors and changes during the year. On the basis of hydrological data recorded from 1979 to 1991 by measurements at stations situated along the deeps of the Southern Baltic, the sound speed has been calculated using the procedure of Chen Millero recommended by UNESCO. The data were averaged in one-months periods and subjected to a detailed analysis of the speed vibrations during the year. The patterns of the sound speed distribution characteristic for every month have been determined. Research was also conducted to find to what extent the synoptic patterns of the sound speed distribution differ from the averaged respective data. To solve the problem, several synoptic distributions established in different seasons are compared with the averaged distribution. Difficulties in specifying the acoustical conditions of the Southern Baltic are augmented by the appearance of short-term local phenomena changing considerably the sound speed distribution in certain areas. Examples of such phenomena are presented in the paper. The paper is based on a large number of in situ measurement data presented in the form of diagrams.